Customer Experience Management in B2B tourism: service business ecosystems - Bermúdez-González, Guillermo José; Ruiz-Alba Robledo, José Luis; López-Tenorio, Pablo J.; Quero-Gervilla, María José (Taylor & Francis, 2025)
This study offers a novel contribution by incorporating the concept of auxiliary service providers (ASPs) into the sharing economy business ecosystem to enhance customer experience management (CXM). The research aims to identify key conditions that facilitate CXM and explore the causal configurations that lead to value co-creation in short-term rentals. A mixed-method approach was employed, combining a focus group, in-depth interviews, and a survey with Airbnb hosts. Data from the survey were analysed using fuzzy-set qualitative comparative analysis (fsQCA). The results reveal that prior knowledge of customer expectations is a necessary condition for effective CXM, and two distinct combinations of conditions can lead to success. These findings underscore the role of ASPs in enhancing professionalism through value co-creation and improved service delivery. The study extends Kumar et al.’s (2018) platform model and contributes to the literature on service ecosystems and collaborative experience design in the sharing economy.
Keywords: Servicio al cliente - Gestión; Marketing industrial; Turismo; Customer experience management; Sharing economy; Platform economy; Value co-creation; Service innovation; Business-to-business